Evaluation of renal traumas according to forensic radiology - Kafadar, Huseyin; Kafadar, Safiye (Annals of Medical Research, 2021)
Aim: The goal of the study is to retrospectively assess cases of renal injuries.Material and Methods: The cases of renal injury presenting at Adiyaman Training and Research Hospital between January 1st, 2013, and December 31st, 2017 were investigated in terms of age, gender, radiologic findings, grade of renal injury, and cause of injury. The degree of kidney injury determined by imaging methods was evaluated in terms of the American Association for the Surgery of Trauma (AAST). Results: Of the 123 patients with renal injury, 27 were female (21.95%) and 96 were male (78.05%), with an average age of 32.6 ± 16.7 years. In total, 59 cases (47.96%) were younger than 35 years. When the cases were examined according to age groups, 11 (8.94%) cases were under the age of 14 years, 23 (18.70%) cases were aged 15–24 years, and 25 (20.32%) cases were aged 25–34 years. The older age groups included 23 (% 18.70) cases aged 35–44 years, 19 (15.46%) aged 45–54 years, 9 (7.31%) aged 55–64 years, and 13 (10.57%) older than 65 years. Overall, 59(47.96%) injuries were from traffic accidents (p0.005), 36 (28.96%) from falls, 12 (9.74%) from sharp and penetrating object injuries, seven (5.69%) from gunshot wounds, five (4.07%) from assaults, and four (3.25%) from work accidents. Conclusion: Renal traumas are life-threatening injuries. We have evaluated renal injuries in terms of radiological and forensic medicine, and we believe the findings contribute to the existing literature on this subject.
Keywords: Forensic medicine; kidney; radiodiagnostic; renal injury; trauma